EFFECTIVENESS AND SUSTAINABILITY OF THE NU COIN MOVEMENT PROGRAM IN ENHANCING COMMUNITY WELFARE - Kiki Yulinda Ningsih; Didik Kusno Aji; Agus Mushodiq (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study examines the persistent issue of poverty within Muslim communities in Indonesia, particularly in Raman Utara District, despite Islamic teachings that emphasize zakat, infaq, and almsgiving as instruments for social welfare. Specifically, the research analyzes the effectiveness of the NU Coin Movement Program in improving community welfare, highlighting the fact that although the program was initially implemented in ten villages, eight of them have stagnated or ceased operations over the past two years. This condition indicates a lack of consistency and sustainability in program implementation. The study employs a qualitative descriptive field research approach. Data were collected through direct observation and semi-structured interviews with beneficiaries, NU Care-LAZISNU administrators, and community leaders in Raman Utara, supported by secondary data from the Central Bureau of Statistics, institutional reports, and academic journals. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing and verification, with data validity ensured through source and method triangulation. The findings reveal that the NU Coin Program has achieved only partial effectiveness, as only two out of ten villages have consistently implemented the program and fulfilled key indicators, including planning, organizing, implementation, and supervision. Transparency in fund management is closely associated with public trust and community participation. Although the program has not yet demonstrated a broad and measurable improvement in overall community welfare, tangible benefits are still perceived by economically disadvantaged groups. Supporting factors include strong leadership, transparent fund management, effective and continuous socialization, and visible social impact, while inhibiting factors involve weak managerial commitment, lack of transparency, ineffective initial socialization, and inconsistent monitoring